Existence of Local Government toward the Implementation of Coaching and Legal Supervision for Franchisee Business - Ika Atikah (Jurnal Cita Hukum, 2018)
AbstractThe growth of franchise business is so fast in Indonesia, involving many local businessmen and foreign businessmen who act as franchisor and franchiser. The development of the franchise business is greatly influenced by the protection of the law by the state. Currently, the legal protection of franchise business activities in Indonesia is regulated in Government Regulation no. 42 of 2007 concerning Franchise and Regulation of the Ministry of Trade of the Republic of Indonesia No. 57/M-DAG/PER/9/2014 concerning Franchise Operation. The role of local government to the local franchise and franchise business activities is very helpful to increase franchise activities to be advanced and as one source of local revenue. The importance of the attention of local governments in the issue of franchise business arrangement is a concrete manifestation of the spirit of regional autonomy. The implementation of regional autonomy focuses more on the role of regional level II (regency/city) as the spearhead of development. From that, coaching and legal supervision on franchise business is the most important part of the implementation of government regulations and trade minister regulations as a form of government concern to the uniqueness of franchise businesses that have distinctive characteristics of business in general.Keywords: Franchise, Local Government, Coaching, Supervision  Abstrak Pertumbuhan bisnis waralaba begitu pesat di Indonesia, melibatkan banyak pengusaha lokal dan pengusaha asing yang berperan sebagai pemberi waralaba dan penerima waralaba. Perkembangan bisnis waralaba sangat dipengaruhi perlindungan hukum oleh negara. Saat ini, perlindungan hukum terhadap kegiatan bisnis waralaba di Indonesia diatur dalam Peraturan Pemerintah No. 42 Tahun 2007 tentang Waralaba dan Peraturan Menteri Perdagangan Republik Indonesia No. 57/M-DAG/PER/9/2014 tentang Penyelenggaraan Waralaba. Peran pemerintah daerah terhadap kegiatan bisnis waralaba lokal dan waralaba asing sangat membantu meningkatkan kegiatan waralaba menjadi maju dan sebagai salah satu sumber pendapatan daerah. Pentingnya perhatian pemerintah daerah dalam masalah pengaturan bisnis waralaba adalah wujud nyata dari semangat otonomi daerah. Pelaksanaan otonomi daerah lebih berfokus pada peran daerah tingkat II (kabupaten/kota) sebagai ujung tombak pembangunan. Berangkat dari hal tersebut, pembinaan dan pengawasan hukum terhadap pelaku bisnis waralaba merupakan bagian terpenting dari pelaksanaan peraturan pemerintah dan peraturan menteri perdagangan sebagai bentuk kepedulian pemerintah terhadap keunikan usaha waralaba yang memiliki ciri khas berbeda dari bisnis pada umumnya.Kata Kunci : Waralaba, Pemerintah Daerah, Pembinaan, Pengawasan. DOI: 10.15408/jch.v6i1.8269